Retorika dakwah ustadzah halimah alaydrus melalui media sosial youtube (analisis pada tema "rumah tangga” dalam channel ustadzah Halimah Alaydrus) - Pridiastuti, Ajeng (Komunika: Journal of Communication Science and Islamic Dakwah, 2022)
Preaching is a noble activity in which a da'i broadcasts the teachings of Islam to mad'u. Therefore, before preaching the da'i should know the strategies to support the success of his da'wah, such as the Science of Rhetoric. Rhetoric is the art or science of the style of language used in conveying a message when speaking in public such as da'wah, speech and others. Ustadzah Halimah Alaydrus is a preacher whose da'wah is currently being heard by Muslimah congregations both offline and online. Ustadzah Halimah when preaching on social media apart from never meeting the congregation directly, she also never showed her face to the congregation online. However, this does not stop the congregation from listening to the da'wah he conveys. This is what makes the writer interested in making it a subject in research. From the background above, the question arises, how is Ustadzah Halimah Alaydrus rhetoric applied? And in this research the author focuses on using the theory of five rhetorical methods written by Zainul Ma'arif in his book Retorika Metode Komunikasi Publik which consists of finding da'wah material (inventio), arranging da'wah texts (dispositio), style of language (elucitio), remembering da'wah material (memoria), and the delivery of da'wah (pronontio). In this research, the author uses a library research method or approach, and based on the results of the rhetorical analysis of Ustadzah Halimah Alaydrus da'wah, the author obtained five rhetorical methods that were applied by Ustadzah Halimah when preaching on youtube social media. The five rhetorical methods of da'wah that she conveys are quite complete, packaged in an attractive manner so that the da'wah material is conveyed correctly, although there are still many shortcomings and these will be described in this research. Abstrak Berdakwah adalah kegiatan yang mulia dimana seorang da'i menyiarkan ajaran agama Islam kepada mad'u. Maka dari itu, sebelum berdakwah da'i hendaknya mengetahui strategi-strategi pendukung keberhasilan dakwahnya, seperti Ilmu Retorika. Retorika merupakan seni atau ilmu tentang gaya bahasa yang digunakan dalam menyampaikan suatu pesan ketika berbicara di depan publik seperti dakwah, pidato dan lainnya. Ustadzah Halimah Alaydrus seorang mubaligh yang saat ini dakwahnya sering didengar oleh jama'ah muslimah baik offline maupun online. Ustadzah Halimah ketika berdakwah di media sosial selain tidak pernah bertatapan langsung dengan para jama'ah, ia juga tidak pernah menampakan wajahnya kepada jama'ah secara online. Tetapi, hal tersebut tidak menutup jama'ah untuk tidak mendengarkan dakwah yang ia sampaikan. Hal tersebut yang membuat penulis tertarik untuk menjadikannya sebagai subjek dalam penilitian. Dari latar belakang di atas timbul pertanyaan, bagaimana penerapan retorika Ustadzah Halimah Alaydrus? Dan dalam penilitian ini penulis fokuskan menggunakan teori lima metode retorika yang ditulis Zainul Ma'arif dalam bukunya Retorika Metode Komunikasi Publik yang terdiri dari menemukan materi dakwah (inventio), mengatur teks dakwah (dispositio), gaya bahasa (elucitio), mengingat materi dakwah (memoria), dan penyampaian dakwah (pronontio). Penilitian ini penulis menggunakan metode atau pendekatan studi analisis isi, dan berdasarkan hasil analisis retorika dakwah Ustadzah Halimah Alaydrus penulis memperoleh lima metode retorika yang diaplikasikan Ustadzah Halimah ketika berdakwah di media sosial yootube. Lima metode retorika dalah dakwah yang ia sampaikan terbilang lengkap, dikemas dengan menarik sehingga materi dakwah tersampaikan dengan benar, walaupun masih banyak kekurangan dan hal tersebut akan penulis jabarkan dalam penilitian ini.